From Human Ecology to Political Ecology: Commercialization of Urban Agriculture in Bandung, Indonesia - Kinanti Indah Safitri; Amir Syamsuadi (Prodi Antropologi Fakultas Ilmu Budaya Universitas Diponegoro, 2026)
Urban agriculture has commonly been analyzed through a human ecology perspective emphasizing its role in food security, resource efficiency and environmental sustainability. However, this approach remains limited in explaining how commercialization transforms urban agriculture into a space shaped by economic and political dynamics. This study aims to examine the shift from a human ecology to a political ecology perspective in understanding the commercialization of urban agriculture in Bandung, Indonesia. This research employs a qualitative case study approach, using in-depth interviews with 25 informants, including urban farmers, government representatives, and private sector actors, complemented by secondary data from various sources. Data were analyzed using thematic analysis to identify patterns related to ecological practices, commercialization processes, and power relations. The findings reveal that urban agriculture in Bandung has transitioned from subsistence-oriented and ecologically grounded practices toward market-driven systems integrated into global supply chains. This transformation is characterized by the emergence of unequal power relations, reduced farmer autonomy, environmental degradation, and the erosion of local ecological knowledge. In conclusion, while human ecology explains the adaptive origins of urban agriculture, political ecology provides a more comprehensive framework to understand its contemporary dynamics. A balanced approach is needed to align economic development with environmental sustainability and social equity.